Les représentations en psychologie du travail, de la formation, et en didactique des disciplines scientifiques - Janine Rogalski (Recherches en Éducation)
The paper proposes a tour d’horizon of the notion of « representation » and the use of the term, in the general framework of cognitive psychology; its polysemy and multidimensional caracteristics are recalled. Two active problematics, from the one hand in cognitive ergonomics and vocational didactics, from the other hand in didactics of scientific fields, are then considered. Firstly, the difference and relationships between “internal” and “external” representations – expressed in various semantic registers – are discussed. Internal representations are “constructs” infered from the subjects’ behaviour (including thiers producing external representations such are verbalisations, drawings, aso.). External representations constitute material representatives of the referent, that can be manipulated within the used register(s). The materialiality of external representations implies the existence of both producing and reducing features, whose didactical effects will be shortly discussed. Secondly, an organisation of several systems of representation will be presented: two were produced by communities of reference (professional or didactical pratices) in a socio-historical process, oriented towards epistemic and pragmatics purposes, a twofold system is concerning the operator’s or student’s mental models, and the last one is related to the analysts activity in their modelisation process of subjects’ mental models. Conclusion opens on two issues: the use external representations as didactical tools, and the status of mental representations in collective activities.